2012
DOI: 10.1177/0959683612460782
|View full text |Cite
|
Sign up to set email alerts
|

A 7000 year record of paleohurricane activity from a coastal wetland in Belize

Abstract: Sedimentary paleotempestological studies have documented that tropical cyclone activity levels in the North Atlantic have been characterized by significant fluctuations since at least the mid Holocene, with activity regimes typically lasting from several centuries to > 2000 years. These activity-level estimates are based on site-specific hurricane strike histories derived from proxy records of overwash events attributed to landfalling major hurricanes. Here we present a 7000 year composite record from two a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 48 publications
2
37
2
Order By: Relevance
“…truncation event most likely associated with a tropical cyclone, a common occurrence within the region (Matyas, 2014). Several large lagoon and embayed water bodies of the US Atlantic show a similar erosional truncation of their fills by tempestite horizons (Liu and Fearn, 1993;McCloskey and Liu, 2013); such a feature need only to form in areas that occur along regular hurricane or cyclone pathways.…”
Section: Stillstand and Highstandmentioning
confidence: 97%
See 1 more Smart Citation
“…truncation event most likely associated with a tropical cyclone, a common occurrence within the region (Matyas, 2014). Several large lagoon and embayed water bodies of the US Atlantic show a similar erosional truncation of their fills by tempestite horizons (Liu and Fearn, 1993;McCloskey and Liu, 2013); such a feature need only to form in areas that occur along regular hurricane or cyclone pathways.…”
Section: Stillstand and Highstandmentioning
confidence: 97%
“…Surface 7 shares many of the attributes of hurricane-generated erosion surfaces identified in similar lagoonal settings (e.g., McCloskey and Liu, 2013). These include the presence of concentrated autochthonous shell debris, capping of the upper surface of the deposit by a lining of concave-up shell layers and an overall fining upward succession.…”
Section: Seismic Stratigraphic Interpretationmentioning
confidence: 98%
“…Such archives have so far provided information as far back as the midHolocene (MH; 7,000-4,000 yBP). Paleotempest records from the western North Atlantic have shown that the frequency of intense hurricanes may have fluctuated considerably during the last 7,000 y under varying climatic conditions (20)(21)(22)(23). However, most of the proxy records span only a few millennia and are limited to specific locations where individual TCs happened to make landfall.…”
mentioning
confidence: 99%
“…These dates were calibrated to calendar years using the Calib 6.0 program (Stuiver, Reimer, and Reimer, 2010), based on the datasets of Reimer et al (2009). An age-depth model was created using a single calendar date for each sample by averaging the midpoints of all sigma date ranges, weighted by probability (McCloskey and Liu, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Three hurricanes (Unnamed, 1931, category 3;Hattie, 1961, category 5;Keith, 2000, category 4) have passed within 10 km at category 3 strength or higher during the last 80 years. Long-term hurricane landfall records indicate that the average strike probability has been~one major storm per decade for the coast of Belize over the last 500 years (McCloskey and Keller, 2009) and that such storms have been frequent occurrences for at least the last 7000 years (McCloskey and Liu, 2013). The effects of Hurricane Hattie, which crossed Turneffe Islands as a category 5 hurricane in 1961, are described in detail by Stoddart (1963).…”
Section: Hurricanesmentioning
confidence: 98%